Leveraging Health Department Capacities, Partnerships, and Health Insurance for Infectious Disease Response in Massachusetts, 2014-2018. (July 2020) - Fukuda, H. Dawn; Randall, Liisa M.; Meehan, Thera; Cranston, Kevin
Policies facilitating integration of public health programs can improve the public health response, but the literature on approaches to integration across multiple system levels is limited. We describe the efforts of the Massachusetts Department of Public Health to integrate its HIV, viral hepatitis, sexually transmitted infection (STI), and tuberculosis response through policies that mandated contracted organizations to submit specimens for testing to the Massachusetts State Public Health Laboratory; co-test blood specimens for HIV, hepatitis C virus (HCV), and syphilis; integrate HIV, viral hepatitis, and STI disease surveillance and case management in a single data system; and implement an integrated infectious disease drug assistance program. From 2014 through 2018, the number of tests performed by the Massachusetts State Public Health Laboratory increased from 16 321 to 33 674 for HIV, from 11 054 to 33 670 for HCV, and from 19 169 to 30 830 for syphilis. Service contracts enabled rapid response to outbreaks of HIV, hepatitis A, and hepatitis B. Key challenges included lack of a billing infrastructure at the Massachusetts State Public Health Laboratory; the need to complete negotiations with insurers and to establish a retained revenue account to receive health insurance reimbursements for testing services; and time to train testing providers in phlebotomy for required testing. Investing in laboratory infrastructure; creating billing mechanisms to maximize health insurance reimbursement; proactively engaging providers, community members, and other stakeholders; and building capacity to transform practices are needed. Using multilevel policy approaches to integrate the public health response to HIV, STI, viral hepatitis, and tuberculosis is feasible and adaptable to other public health programs.